Consumo de nutrientes, produção e composição do leite de ovelhas e desempenho de cordeiros oriundos de parto simples ou duplo - Wommer, Tatiana Pfuller (2010)
The experiment was conducted in the Sheep Division of the Universidade Federal de Santa Maria (UFSM) to determine nutrient intake, and yield and composition of milk from ewes, as well as its relationship with performance and carcass characteristics of either single or twin lambs. Sixteen multiparous ewes from an alternate crossing between Texel and Ile de France breeds were used. Eight ewes supported single lambs, and the others supported twin lambs. Animals (ewe + lambs) were allocated in individual stalls immediately after parturition, and the milk production was then estimated weekly. Protein, fat, lactose, total solids, and milk density were determined in the milk samples. At 56 days of age all animals were weaned and 16 lambs (8 single and 8 twin lambs) were randomly selected and maintained in individual stalls until reaching a pre established slaughter weight, which was approximately 28 kg of body weight. Qualitative and quantitative measures were then done on the carcasses and on every other body component. There was no effect (P<0.05) of the number of suckling lambs on nutrient intake, milk yield and composition of the ewe s milk. However, nutrient intake linearly increased (P<0.05) as a function of the time in the experiment. Single lambs presented higher body weights at both birth and weaning (P<0.05), as well as they had greater average daily gain from the birth to the weaning (P<0.05). The better performance of these animals, however, was not maintained after the weaning. Twin lambs presented greater nutrient intake when it was calculated as a percentage of the BW and in g/kg BW0.75, resulting in a highest proportion (P<0.05) of rumen in relation to the body weight of the animals. On the other hand, single lambs had more elevated values of carcass dressing percentage (P<0.05). Results showed that due the similarity between milk yields of ewes supporting either single or twin lambs, before the weaning single lambs present a potential of growth higher than that of twin lambs, once the individual milk intake is also more elevated for these animals. Thus, the slaughter weight is reached early and the carcasses have better quality.